Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Tri Hita Karana pada Kinerja LPD - Suarna Bumi, I Putu; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
The study aimed to examine the influence of the transformational leadership style and culture of Tri Hita Karana on the performance of the Village Credit Institutions (LPD) in Denpasar, which amounted to 35 LPD. Respondents used in the study were the head of the LPD, the administrative staff, and the cashier. Overall respondents numbered 105 people who were determined using the saturated sample method. Data collection methods and data analysis techniques used are questionnaire methods and multiple linear regression analysis. The results showed that the transformational leadership style apparently had a negative influence on LPD performance, inversely proportional to the culture of Tri Hita Karana which had a positive influence on LPD performance in Denpasar City. Keywords : Performance; Leadership; Tri Hita Karana.